2015
DOI: 10.1175/jas-d-14-0151.1
|View full text |Cite
|
Sign up to set email alerts
|

Are Eyewall Replacement Cycles Governed Largely by Axisymmetric Balance Dynamics?

Abstract: The authors question the widely held view that radial contraction of a secondary eyewall during an eyewall replacement cycle is well understood and governed largely by the classical theory of axisymmetric balance dynamics. The investigation is based on a comparison of the secondary circulation and derived tangential wind tendency between a full-physics simulation and the Sawyer-Eliassen balance model. The comparison is made at a time when the full-physics model exhibits radial contraction of the secondary eyew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Such waves are difficult to see in observations; Corbosiero et al (2006) used radar reflectivity over several hours with 5-min temporal and 750-m spatial resolution over 150 km of radius to identify these features. A numerical simulation by Abarca and Corbosiero (2011) made similar arguments on the role of Rossby waves on ERCs. In principle, this process could create a secondary eyewall because the increase in cyclonic flow from the momentum accumulation can enhance surface fluxes, convection, and cyclonic vorticity.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…Such waves are difficult to see in observations; Corbosiero et al (2006) used radar reflectivity over several hours with 5-min temporal and 750-m spatial resolution over 150 km of radius to identify these features. A numerical simulation by Abarca and Corbosiero (2011) made similar arguments on the role of Rossby waves on ERCs. In principle, this process could create a secondary eyewall because the increase in cyclonic flow from the momentum accumulation can enhance surface fluxes, convection, and cyclonic vorticity.…”
Section: Introductionmentioning
confidence: 65%
“…Considerable controversy exists as to whether the boundary layer processes in the outer eyewall are balanced or unbalanced (Rozoff et al 2012;Huang et al 2012;Kepert 2013;Montgomery 2014, Abarca andMontgomery 2015;Wu et al 2016), but there is little doubt that the resulting contracting outer eyewall is based in the boundary layer.…”
Section: Introductionmentioning
confidence: 99%
“…Detecting and tracking the rotational center of tropical cyclones (TC) are critical for objective TC-intensity estimation [1,2], the detection of rapid intensification [3], dynamic diagnosis [4][5][6] and TC climatological descriptions [7][8][9][10][11]. Studies have shown that the overall conclusions could be heavily sensitive to the accuracy of the center [12,13], because positioning the center is the initial step in most of the applications.…”
Section: Introductionmentioning
confidence: 99%
“…Strong TCs often have been observed with an inner (primary) and outer (secondary) eyewall separated by a region of minimal convection (Willoughby et al 1982). Although variable and not always completed, the ERC typically begins with the formation of the outer eyewall, continues as convection intensifies in the outer eyewall and weakens in the inner eyewall, and concludes as the inner eyewall fully decays and the outer eyewall contracts toward the storm center (Rozoff et al 2008;Sitkowski et al 2011;Kossin and Sitkowski 2012;Abarca and Montgomery 2013). Important intensity changes occur concurrently with these changes in convective structure, so much so that Sitkowski et al (2011) classified ERCs into three intensity-based phases: intensification, weakening, and reintensification.…”
Section: Introductionmentioning
confidence: 99%
“…One of the objectives of the current study is to present a geostationary satellitebased technique that highlights the structural evolution of deep convection during the ERC of Typhoon Sinlaku (2008). Given the role of boundary layer dynamics in ERCs [e.g., the boundary layer spinup mechanisms proposed by Abarca andMontgomery (2014, 2015)], another objective is to compare the evolution of deep convection with the concurrent evolution of the surface and flight-level wind measurements within and above the boundary layer, respectively. The surface winds were measured by the Stepped-Frequency Microwave Radiometer (SFMR), and the flight-level winds were computed by the aircraft data system, both on board the WC-130J.…”
Section: Introductionmentioning
confidence: 99%